Model Test Study on Deformation of Snowflake Shaped Steel Sheet Pile Based on OFDR - Lei Gao (MDPI AG, 2021)
As a newly developed pile foundation, the snowflake shaped steel sheet pile is composed of three Y-shaped sections with an included angle of 120° and has a large specific surface area, which can give full play to the side friction of pile and improve the bearing capacity of single pile. At the same time, the snowflake shaped steel sheet pile has a high strength, relatively few materials, and it has good prospects with engineering applications. In order to accurately grasp the mechanical characteristics of the snowflake shaped steel sheet pile, this paper carried out the model test of snowflake shaped steel sheet pile based on OFDR (optical frequency domain reflector) distributed optical fiber sensor technology. The results show that: (1) OFDR distributed optical fiber sensing technology can effectively monitor the strain of snowflake steel sheet pile; (2) under the vertical load, the strain of snowflake steel sheet pile decreases along the length of the pile; (3) the strain of the same section of snowflake steel sheet pile is different at different positions, the strain at the junction between web and web is basically the same as the junction between web and flange, and the strain of the pile shaft on the flange edge is larger.